2017
DOI: 10.1007/s00213-017-4686-6
|View full text |Cite
|
Sign up to set email alerts
|

5-HT modulation of pain perception in humans

Abstract: IntroductionAlthough there is clear evidence for the serotonergic regulation of descending control of pain in animals, little direct evidence exists in humans. The majority of our knowledge comes from the use of serotonin (5-HT)-modulating antidepressants as analgesics in the clinical management of chronic pain.ObjectivesHere, we have used an acute tryptophan depletion (ATD) to manipulate 5-HT function and examine its effects of ATD on heat pain threshold and tolerance, attentional manipulation of nociceptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 83 publications
3
29
1
3
Order By: Relevance
“…Praying by focusing one's attention and thoughts on God followed by acupoint stimulation through affirmation-taping will increase the level of serotonin (Liu, Tan, Molassiotis, Suen, & Shi, 2015;Ménard, Pfau, Hodes, & Russo, 2017). This will modulate their pain perception (Martin et al, 2017). Affirmations using prayers that are uttered with sincerity and confidence can double the empowerment in the forebrain and amygdaloid, boosting performance so then the function of pain control becomes better and more effective (Beiranvand, Noparast, et al, 2014;Fajarudin, 2006;H.M.…”
Section: Discussionmentioning
confidence: 99%
“…Praying by focusing one's attention and thoughts on God followed by acupoint stimulation through affirmation-taping will increase the level of serotonin (Liu, Tan, Molassiotis, Suen, & Shi, 2015;Ménard, Pfau, Hodes, & Russo, 2017). This will modulate their pain perception (Martin et al, 2017). Affirmations using prayers that are uttered with sincerity and confidence can double the empowerment in the forebrain and amygdaloid, boosting performance so then the function of pain control becomes better and more effective (Beiranvand, Noparast, et al, 2014;Fajarudin, 2006;H.M.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested a complex role of 5-HT in the modulation of pain [45]. Research by Martin et al [46] found that acute TRP depletion decreased both heat pain tolerance and threshold. Furthermore, acute TRP depletion was reported to decrease brain 5-HT levels, and to increase visceral perception and negative emotional bias in patients with irritable bowel syndrome [47].…”
Section: Tryptophanmentioning
confidence: 95%
“…At higher doses (approximately 15-45 mg/kg), caffeine augments antinociception by acetaminophen and others non-steroidal anti-inflammatory drugs (NSAIDs) and produces intrinsic antinociception in some preclinical models. At even higher doses polyphenols [23][24][25][26][27][28][29], methylxanthines [32,33], Nacylethanolamines [34][35][36], biogenic amines [36][37][38], alkaloids [39][40][41][42], and tryptophan [43][44][45][46][47][48] of the central adenosine receptors A2B and A2A, and of the microglial COX [32].…”
Section: Methylxanthinesmentioning
confidence: 99%
“…Впливає на патогенез депресивних станів та неврозів [37]. У фаховій літературі містяться дані про виражений антистресорний ефект L-триптофану, корегуючий вплив на больову перцепцію [36][37][38][39][40]. Крім того, для зменшення функціональної активності симпатичної нервової системи пацієнти упродовж 7 днів до операцій та за 30 хв до їх початку приймали ендоназально розчин даларгіну (синтетичний аналог лейцин-енкефаліну) -1 мг сухої речовини, розчиненої в 0,5 мл 0,9 % хлориду натрію.…”
Section: оцінка ефективності антистресорного захисту хірургічних стомunclassified